2022
DOI: 10.1038/s41598-022-23492-3
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of lambda-cyhalothrin on Musca domestica L. (Diptera: Muscidae)

Abstract: The hormetic effect may cause disease control measures to fail due to inadequate treatment of human disease vectors such as houseflies. Age-stage, two-sex life table is used for accurate estimation of the hermetic impacts on insects as it allows to study sub-lethal or transgenerational effects. Pyrethroids insecticides are primarily used for the management of houseflies. This study used lambda-cyhalothrin (a pyrethroid insecticide) to quantify its transgenerational impacts on houseflies. Life table parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In line with these data, Zhang et al [ 41 ] previously observed a pronounced reduction in these demographic parameters in the F 1 generation of R. padi after exposure of the parental generation of aphids to beta-cypermethrin at an LC 10 concentration level. Moreover, Ghramh et al [ 50 ] reported significant decreases in demographic parameters of the F 1 generation of M. domestica following parental exposure to LC 10 and LC 30 concentrations of LCT relative to the control group. Members of the F 1 generation in the insecticide-treated groups also exhibited significantly reduced f xj , m x , l x m x , e xj , and v xj values relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, Zhang et al [ 41 ] previously observed a pronounced reduction in these demographic parameters in the F 1 generation of R. padi after exposure of the parental generation of aphids to beta-cypermethrin at an LC 10 concentration level. Moreover, Ghramh et al [ 50 ] reported significant decreases in demographic parameters of the F 1 generation of M. domestica following parental exposure to LC 10 and LC 30 concentrations of LCT relative to the control group. Members of the F 1 generation in the insecticide-treated groups also exhibited significantly reduced f xj , m x , l x m x , e xj , and v xj values relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The transgenerational studies were conducted using the methodology of Ghramh et al [26]. Briefly, LC 25 and LC 50 concentrations of pyriproxyfen were prepared in 20% sugar solution and 50 adults (4-5 days old) were exposed to each concentration.…”
Section: Transgenerational Studiesmentioning
confidence: 99%
“…After hatching, the larvae were reared in the same groups in small plastic boxes (4×15×10 cm) until adult eclosion at 25± 2˚C under a 16:8 h light-dark photoperiod and 60±5% relative humidity. After adult emergence (F1), pre-oviposition period, oviposition period and fecundity were determined following the methodology of Ghramh et al [26].…”
Section: Transgenerational Studiesmentioning
confidence: 99%
“…Overall, both insecticides caused more than half the population death of house flies within 48 hours. However, Ghramh, et al, (2022) studied lambada-cyhalothrin for the management of house flies. Also, on life table parameters of the progenitor of adult houseflies exposed to LC10, Lc30 and LC50 of Lambada-cyhalothrin.…”
Section: Fig (9 G1mentioning
confidence: 99%